A comprehensive review of plant-based meal replacements as a low-calorie solution for weight management - Nurizzati, Nurizzati Y; Aida , Aida FMNA; Nur Shahirah N; Raseetha , Raseetha S; Ahmad Zahin Ilman O; Nor Ashikin Z; Abzar, A Abzar; Rasyiqah Nabihah Binti Roslli (Hasanuddin University Food Science and Technology Study Program, 2026)
Meal replacement can be the preferred option over the regular meal during breakfast, lunch, and dinner. The convenience of meal replacement products contributes to the popularity not only for working adults, but meal replacement also appeals to individuals with hectic schedules and those juggling household responsibilities. Meal replacement products often contain a combination of important nutrients focused on providing a balanced and convenient alternative to traditional and regular meals. These products typically include a combination of protein, carbohydrates, healthy fats, vitamins and minerals, as well as dietary fibres to meet the nutritional requirements of the body. There are also a number of meal replacement products with distinct ingredients to fit the preferences of the individuals. Despite its popularity, there are still different perceptions of individuals towards meal replacement products. In this review, the types of meal replacement products as well as the ingredients and benefits of the meal replacements and traditional meal has been compared. Furthermore, the effectiveness of meal replacement intake on satiety has also been studied. Satiety is defined as the period between meals that reduces appetite and discourages overeating. Besides that, the effectiveness of meal replacement products on weight loss and metabolic health has been explored. Finally, the benefits and drawbacks of meal replacement products has been discussed in detail.